THE EFFECTS OF THE USE OF SERIES CARD MEDIA ON TOILET TRAINING SKILL TOWARD AUTISM CHILDREN - Ida Nauli Nainggolan; Agung Kurniawan (Department of Special Education, 2016)
The Effects of the usage of series images card media on toilet training skill toward autistic children. This research was aimed at describing the effects of the used of series images card media on toilet training toward autistic children. This research used experimental approach in the form of Single Subject Research (SSR), using the A-B-A’ design. The result of the research showed that the series images card media had effects on autism child toilet training skill. Pengaruh Penggunaan Media Kartu Gambar Berseri terhadap Keterampilan Toilet Training (BAK) Siswa Autis. Penelitian ini bertujuan untuk mendeskripsikan pengaruh penggunaan kartu gambar berseri terhadap ketrampilan toilet training anak autis. Metode yang digunakan dalam penelitian ini adalah metode eksperimen dengan menggunakan Single Subject Research (SSR). Dalam penelitian ini desain yang digunakan adalah desain A-B-A’. Hasil penelitian menunjukkan bahwa media kartu gambar berseri toilet training berpengaruh terhadap kemampuan toilet training anak autis.